A Cross-Sectional Study Investigating Primary School Children's Coding Practices and Computational Thinking Using ScratchJr. (March 2022) - Kyza, Eleni A.; Georgiou, Yiannis; Agesilaou, Andria; Souropetsis, Markos
There are increasing calls to introduce computational thinking in schools; the arguments in favor call upon research suggesting that even kindergarten children can successfully engage in coding. This contribution presents a cross-sectional study examining the coding practices and computational thinking of fifty-one primary school children using the ScratchJr software; children were organized in two cohorts (Cohort 1: 6–9 years old; Cohort 2: 10–12 years old). Each cohort participated in a six-hour intervention, as part of a four-day summer club. During the intervention children were introduced to ScratchJr and were asked to collaboratively design a digital story about environmental waste management actions, thus adopting a disciplinary perspective to computational thinking. Data analyses examined children's final artifacts, in terms of coding practices and the level of computational thinking demonstrated by each cohort. Furthermore, analysis of selected groups' storyboard interviews was used to shed light on differences between the two cohorts. Results are presented and contrasted across the two age cohorts via a developmental perspective. The findings of this study can be useful in considering the instructional support that is necessary to scaffold the development of primary school children's coding practices and computational thinking.